1994
DOI: 10.1002/ldr.3400050304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the characteristics of 14 cover crops used in a soil rehabilitation trial

Abstract: Many of the soils in Santa Cruz Department, Bolivia, are degraded by serious weed infestation, subsoil compaction, and low organic matter and nitrogen contents. Fallow periods with cover crops are frequently used to recuperate the fertility of degraded soils, but little information exists on the desired characteristics of cover crops for this purpose. The aim of this study was to describe those characteristics, believed to be most relevant to the rehabilitation of degraded soils in Santa CNZ, of 14 cover crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…In 2004, during rest in the AV treatment, erosion increased six-fold, much more than in the IT and TO treatments; nevertheless, the recorded value of (1.5 Mg ha À1 y À1 ) can be ranked as slight to moderate erosion. The latter result, and the increased surface runoff, strengthens the need for evaluating crops that favor soil rehabilitation during the fallow in Acrisols, as suggested by Barber and Navarro (1994), and demonstrated by Fuentes et al (2009) when the greatest effects on the soil's physical-chemical properties was produced by a maize-wheat rotation in Central Mexico.…”
Section: Soil Lossesmentioning
confidence: 67%
See 1 more Smart Citation
“…In 2004, during rest in the AV treatment, erosion increased six-fold, much more than in the IT and TO treatments; nevertheless, the recorded value of (1.5 Mg ha À1 y À1 ) can be ranked as slight to moderate erosion. The latter result, and the increased surface runoff, strengthens the need for evaluating crops that favor soil rehabilitation during the fallow in Acrisols, as suggested by Barber and Navarro (1994), and demonstrated by Fuentes et al (2009) when the greatest effects on the soil's physical-chemical properties was produced by a maize-wheat rotation in Central Mexico.…”
Section: Soil Lossesmentioning
confidence: 67%
“…Several authors have recognized the need for improving traditional fallow systems in degraded soils by the use of species that accumulate or recycle larger amounts of nutrients, or that better promote the restoration of the physical properties of soils (Barber and Navarro, 1994;Kass and Somarriba, 1999;Barrios et al, 2005). Assessments of alternative management methods such as crop rotations, intercropping systems, minimum-or zero-tillage approaches, and the management of crop residues for the restoration of soil quality, have been made in regions with predominance of traditional soil management systems (Huang et al, 2006;Fuentes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…During three months growth in a pot experiment, Joseph (1970) estimated the N fixation of Pueraria to 65 kg ha -1 . Despite the fact that the legume cover crops have a large biomass production and turnover, they are not likely to increase the soil organic matter content (Barber & Navarro, 1994a). However, Tian et al (1999) reported a lower soil organic matter decline with a Pueraria simultaneous cropping system than with conventional cropping in Nigeria.…”
Section: Biomass Production and Nutrient Turnovermentioning
confidence: 99%
“…Whereas ample information exists about cover crops in crop rotations (e.g. Barber & Navarro, 1994a), forage legumes (e.g. Cadisch et al, 1989) or intercropping with annual crops (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples of their wide-spread use in intensive agriculture (Stivers et al, 1993;Reeves, 1994) and in increasing or sustaining the productivity of smallholder farming systems (Prinz, 1986). They have been particularly successful in combating soil degradation on sloping land; on land that was cleared and impoverished in slash and burn agriculture; and on land continuously cropped with cereals (Wilson et al, 1982;Barber and Navarro, 1994). Recent initiatives to increase the use of legume cover crops in agricultural practices worldwide have been discussed by Swift et al (1997).…”
Section: Introductionmentioning
confidence: 99%